(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
Financing terrorist activity is the true nerve of terrorist operations, from it these operations derive their human and material strength, as financing terrorism, in other words, is the blood that flows through the veins of terrorist organizations. The escalation of violence and terrorism is clearly evident with the escalation of funding, as the volume of terrorist financing has expanded in Algeria or elsewhere despite the presence of legislative texts related to combating it, which raised questions about its effectiveness and sufficiency. Algerian concerned to combat it.